A study on the Effects of LMX in team context: The moderating effects of LMX differentiation and TMS - Oh, WonKyung; Kim, MinSoo (Korean Journal of Industrial and Organizational Psychology, 2012)
The previous LMX literatures have studied that leader’s differential role influenced member’s attitude in leader and member dyadic relationship. But after the study of Sparrowe & Liden(1997), the recent literature emphasize the necessity of multilevel approach, focusing on the team context that belongs leader and members beyond independent dyadic relationship. So we explored ‘LMX differentiation’ and ‘TMS’ as team context factor that influenced employee in team. These factors extend LMX research in that team context could be consider as boundary condition in relationship. To test multilevel hypothesis, we collected the survey data from 277 members and 37 teams and analyzed Hierarchical Linear Modeling. In result, We found that employee’s LMX quality increases team commitment and TMS quality moderate that relationship.